“FORMULATION AND EVALUATION OF TRANSDERMAL PATCHES OF PREDNISOLONE” - C, Chirayu.; T.S, Nagaraja; Vijapure, Vitthal K (Journal of Biomedical and Pharmaceutical Research, 2019)
The purpose of this research work was to develop and evaluate transdermal patch of Prednisolone, using Xanthan gum, Guar gum and Polyacrylamide in different ratios prepared by the Glass Substrate Technique. The physicochemical compatibility of the polymers and the drug was evaluated by FTIR. The results suggested that no physicochemical incompatibility between the polymer and the drug. Drug free films were formulated and evaluated characteristics like flexibility and smoothness. Further drug loaded films were formulated and evaluated for thickness, weight uniformity, drug content, folding endurance and drug release. The XRD analysis confirmed the amorphous dispersion of the drug in the formulation. SEM analysis showed surface morphology of prepared formulations. Drug diffusion through cellophane membrane was carried out using Franz diffusion cell by in-vitro study. The film prepared with formulation PDS 9 showed maximum diffusion release at the end of 24 hours. It is shown that drug release follows order and non Fikinian mechanism of release diffusion. The PDS 9 formulation was found to be stable with respect to drug content as well as physical changes at 40 ºC and 75 % RH.Keywords: Transdermal drug delivery, Prednisolone, Xanthan gum, Guar gum, Polyacrylamide.